Thermochemical measurement of the ligand field splitting energies for hexaaquocopper (II) and hexaamminecopper (II) ions - Muhammad Badri; Jamieson, James W. S. (N R C Research Press, 1979)
The vacuum dehydration of copper (II) sulphate pentahydrate has been shown to pass through the transitory tryhydrate state before proceeding to the monohydrate composition. Based on this, the heat of solution data for the high-energy modification hydrates have been reinterpreted and the low-energy crystalline hydrates of various compositions have been prepared and their heats of solution measured. From the heat of solution data the maximum energy difference expressed in kcal/mol heptahydrate appears to be of the right order of magnitude to be regarded as the ligand field splitting energy for the hexaaquocopper (II) ion. Similar measurement for the ammine complexes of copper (II) sulphate has also been done and the maximum energy difference was found to agree well with the value of LFSE obtained by spectroscopic method.